Can Reputation Discipline the Gig Economy? Experimental Evidence from an Online Labor Market - Alan Benson; Aaron J. Sojourner; Akhmed Umyarov (Institute for the Study of Labor (IZA), 2015)
In two experiments, we examine the effects of employer reputation in an online labor market (Amazon Mechanical Turk) in which employers may decline to pay workers while keeping their work product. First, in an audit study of employers by a blinded worker, we find that working only for good employers yields 40% higher wages. Second, in an experiment that varied reputation, we find that good-reputation employers attract work of the same quality but at twice the rate as bad-reputation employers. This is the first clean, field evidence on the value of employer reputation. It can serve as collateral against opportunism in the absence of contract enforcement.
Keywords: L14; M55; J41; J2; L86; D82; K12; K42; 330; labor; personnel; contracts; online labor markets; job search; screening; reputation; online ratings